KOMPLEKS KEAMANAN REGIONAL INDO-PASIFIK SEBAGAI FAKTOR PEMICU PEMBENTUKAN AUKUS - Pradono Budi Saputro; Alessandro Kurniawan Ulung; Muhammad Abdurrohim (Halu Oleo University, 2024)
The Indo-Pacific region is currently at risk of developing into a regional security complex. The Indo-Pacific saw a rise in enmity patterns among states in this region. This issue arises because China’s more assertive regional policy, especially the United States, makes other states uneasy. This paper questioned whether China’s aggressiveness was the only factor driving the establishment of AUKUS. Using a qualitative method with interpretative analysis, this paper, therefore, aims to research further the Indo-Pacific’s rising amity and enmity patterns that led to the AUKUS establishment. The authors will employ four variables from Barry Buzan and Ole Wæver’s regional security complex theory, namely boundary, anarchic structure, polarity, and social construction, to comprehend and explain these patterns. Based on the findings, the authors concluded that each of these four variables played a part in changing the Indo-Pacific strategic environment and encouraged the United States, the United Kingdom, and Australia to deepen their partnerships through AUKUS.